Financial Inclusion and Financial Technology in SMEs: Investigating the Mediating Role of Risk Perception on Business Performance - Divia Lasasyauma Purnasalam; Embun Suryani (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2025)
Purpose: This study examines the impact of financial technology and financial inclusion on the performance of small and medium-sized enterprises (SMEs) in the creative economy sector with risk perception serving as a mediating variable.Method: Data collection was conducted through surveys and questionnaire distribution to participants. The study involved a sample of 130 SMEs operating in the creative sector on Lombok Island that utilize financial technology in their businesses. A combination of purposive and accidental sampling techniques was employed. The data were analyzed using structural equation modeling with the partial least squares (SEM-PLS) approach.Result: The findings reveal that financial technology has no significant impact on risk perception, while financial inclusion demonstrates a significant effect. Similarly, financial technology does not significantly influence SME performance, whereas financial inclusion has a substantial impact. Risk perception exhibits only a minor effect on SME performance. Furthermore, risk perception does not mediate the relationship between financial technology and SME performance, nor does it mediate the relationship between financial inclusion and SME performance.Practical Implications for Economic Growth and Development: This study highlights the importance of financial inclusion in enhancing SME performance, suggesting that greater access to financial services can drive economic growth by improving business efficiency and market competitiveness. Furthermore, it emphasizes the need for policies that foster financial inclusion to support sustainable development in the creative economy sector.